2010
DOI: 10.3109/19396360903515430
|View full text |Cite
|
Sign up to set email alerts
|

DNA Fragmentation Dynamics in Fresh Versus Frozen Thawed Plus Gradient-Isolated Human Spermatozoa

Abstract: The aim of this study was to compare the rate of sperm DNA fragmentation (rSDF; increase of SDF over time) in fresh and gradient isolated frozen-thawed semen samples from male sperm donors of proven fertility. SDF was assessed in the two samples obtained from the same fifteen male donors after 0.5, 1.5, 4.5, 6, 24, 48, and 72 h of incubation in a humidified atmosphere of 5% CO 2 in air at 371C. Analysis was performed based on chromatin dispersion patterns evaluated using the Halosperms kit. No significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…12 An aliquot of 50 ml of each DGC-recovered semen sample was used for the SDF assessment. To avoid the undesirable effect of iatrogenic DNA damage to the sperm after processing, which produces a variable and dynamic increase in SDF values, 13,14 all sperm samples were assessed for SDF immediately after sperm selection.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…12 An aliquot of 50 ml of each DGC-recovered semen sample was used for the SDF assessment. To avoid the undesirable effect of iatrogenic DNA damage to the sperm after processing, which produces a variable and dynamic increase in SDF values, 13,14 all sperm samples were assessed for SDF immediately after sperm selection.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…This is an important aspect of the study, since DNA damage, far from being a static parameter, increases as the samples are incubated in vitro. This effect is observed both in fresh 38 and in cryopreserved thawed samples. 39 Consequently, the observed values at the time of ICSI fertilisation can be very different to those assessed before or after the time of fertilisation.…”
Section: Oocytes and Spermatozoamentioning
confidence: 80%
“…Congruent with this idea are those reports claiming that the predictive value of SDF is low when ICSI is used. 14,15,21 It should be noted that while the incidence of SDF in the selected population may in fact decline after sperm selection, there is still a reasonable chance of accidently selecting one of the remaining underlying sub-population of DNA damaged spermatozoa that was not initially excluded in the selection procedure, i.e., a certain level of damaged spermatozoa still remains in the sample, even under the most stringent and rigorous conditions for sperm selection (see data in Zini et al 42 Gosálvez et al 38 and Enciso et al 43 ). By way of an example, if we analyse the data shown by Santiso et al 48 in Figure 1, in some cases and after a swim-up procedure, we are selecting sperm subpopulations containing shorter telomeres than those considered as normal.…”
Section: Sperm Selection and Sperm Dna Damagementioning
confidence: 99%
See 1 more Smart Citation
“…However, it has still not been clearly established whether there exists a direct relationship between cryopreservation and sperm DNA damage. Gosálvez et al (2010), suggest that the incidence of increased single-and/or double-stranded DNA breaks following cryopreservation is not a direct consequence of the freezing process, but rather, that modifications to the chromatin-SNBP interaction as a result of freeze-thawing predisposes the sperm DNA to fragmentation that manifests, not immediately, but over time following thawing. In most mammalian species, including but not limited to the koala (Johnston et al 2012a), stallion ), ram and Asian elephant (Elephas maximus; Imrat et al 2012), the basal level of sperm DNA damage observed immediately after thawing does not differ significantly from that observed in fresh spermatozoa.…”
Section: The Effect Of Cryopreservation On Dna Integritymentioning
confidence: 99%